Pengaruh Gaya Kepemimpinan Demokratis Kepala Sekolah, Kompetensi Guru dan Manajemen Kelas terhadap Mutu Pembelajaran - Comalasari, Enny; Harapan, Edi; Houtman, Houtman (Yayasan Sembilan Pemuda Indonesia, 2020)
This study examined 1) the influence of democratic leadership headmaster toward learning quality, 2) the influence of teacher’s competence toward learning quality, 3) the influence of class management toward learning quality, and 4) the influence of democratic leadership of headmaster, teacher’s competence, and class management toward learning quality of SMP Negeri in Indralaya Selatan. This research used quantitative methods. Data collected through questionnaire, and documentation. Data were analyzed descriptively using SPSS version 16 for windows. The results concluded that there is significant influence of democratic leadership of headmaster, teacher’s competence, and class management toward learning quality of SMP Negeri in Indralaya Selatan.